Mixed Infection Is Common in Children with Respiratory Adenovirus Infection - KORPPI, M. (Acta Paediatr, 2008)
ABSTRACT. The presence of concomitant viral or bacterial infection was evaluated in 20 patients hospitalized for adenovirus infection of the middle or lower airways by using new serological methods for detection of both antigens and antibodies. Adenovirus infection was identified by measurement of antibodies with complement fixation test or by direct detection of viral antigen in nasopharyngeal aspirates. Mixed infection was present in 11 (55%) of the 20 patients. Viral coinfection was demonstrated in five (25%) and bacterial in nine (45%) patients. Bacterial coinfection was common, 67%, in children with an infection focus, pneumonia or acute otitis media, but rare, 13%, in those without it. Seroconversion to nontypable Haemophilus influenzae was indicated in six children; four of them were infants, four had pneumonia and three acute otitis media. Pneumococcal infection was indicated in two patients with pneumonia, both aged over two years. Chlamydia trachomatis was involved in one case. The results indicate that bacterial coinfection is common in respiratory adenovirus infection affecting lower airways, especially if pneumonia is present.